If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + -198 = 6x + -8 Reorder the terms: -198 + 16x = 6x + -8 Reorder the terms: -198 + 16x = -8 + 6x Solving -198 + 16x = -8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -198 + 16x + -6x = -8 + 6x + -6x Combine like terms: 16x + -6x = 10x -198 + 10x = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 -198 + 10x = -8 + 0 -198 + 10x = -8 Add '198' to each side of the equation. -198 + 198 + 10x = -8 + 198 Combine like terms: -198 + 198 = 0 0 + 10x = -8 + 198 10x = -8 + 198 Combine like terms: -8 + 198 = 190 10x = 190 Divide each side by '10'. x = 19 Simplifying x = 19
| 2x^2-345=3456 | | 8x+27=2x+99 | | 88-5x=22x+16 | | 4x^2-60x+216=0 | | 150/-30= | | 25x^2-35=1 | | 174-6x=39x+24 | | 2x+40=12x-50 | | 7x-(2-1)(4x+5)= | | 5a^2-25a+30=0 | | x-3x=-40 | | -48-2x=6-8 | | -10-(-21)+(-5)-15= | | 4x-0.1*(x^2)=8 | | 6x+39=13x-45 | | 2s^2=8s | | 104-4x=14x+18 | | 8x-2x+7-2(2x-3)=6x-3-(x-6) | | -44-7x=88x+16 | | -8+6+(-3)= | | 1x+3x=40 | | 188-6x=30x+16 | | -3(2x-5)+7=(3-x) | | 103-4x=4x+7 | | T=3m+3z | | -3(2x-5)7=(3-x) | | x+(x+3)=23 | | 3x-2=80 | | x/0.6=9.3 | | 6x+12-7=41 | | 6k-4=2k+8 | | -2+3y=12 |